Aktinomikoza - Pirš, Mateja (Medicinski razgledi, 2003)
Actinomycosis is a rare, slowly progressive infection caused by Gram-positive anaerobic bacteria from the Actinomyces genus. The disease is characterized bythe formation of abscesses surrounded by dense fibrosis that slowly spread across natural anatomic boundaries. Actinomycosis can affect virtually any site in the body, and is commonly confused with a neoplasm. The disease is treated with high doses of antibiotics for a prolonged period of time. In moreadvanced cases, a combination of an antibiotic and surgical therapy is commonly used.
Keywords: Aktinomikoza; Actinomycosis; Absces; Actinomyces; Aktinomikoza cervikofacialna; Classification; Centralno živčevje, bolezni; Pathogenicity; Lung Diseases; Medenična bolečina; Penicilini; Diagnosis; Etiology; Pljuča, bolezni; Trebušni absces; Actinomycosis, Cervicofacial; Complications; bakterijske infekcije; Abscess; zdravljenje; therapy; Abdominal Abscess; Pelvic Pain; Central Nervous System Diseases; Penicillins; diagnostika